Facts about Vitamin B6 - Anne Kendall (EDIS)
FCS8700, a 2-page fact sheet by Anne Kendall, explains the importance of vitamin B6 and lists needed amounts for different populations and amounts found in common foods. Published by the UF Department of Family, Youth and Community Sciences, July 2006.